Analysis of Working Capital Credit in the Construction Sector at PT Bank Tabungan Negara Makassar Branch - Ainun Sartika Kinar; Muryani Arsal; Amelia Rezki Septiani Amin (Yayasan Amerta Insan Unggul, 2026)
This research aims to analyze the provision of Working Capital Credit (KMK) in the construction sector by PT Bank Tabungan Negara (BTN) Makassar Branch. This research uses a qualitative descriptive approach with data obtained through interviews, observation, and documentation. The focus of the research includes credit granting procedures and identifying the obstacles faced in its implementation. The research results show that BTN has implemented systematic credit procedures, starting from the application process, followed by a feasibility analysis based on The 5C principles (Character, Capacity, Capital, Collateral, and Condition), and finally, the credit disbursement process. The Working Capital Credit helps construction entrepreneurs meet their project needs, such as purchasing materials and paying workers' wages, thereby enabling the smooth running of construction activities. However, the study identifies several obstacles, including customers' lack of understanding of credit procedures and the risk of bad credit resulting from suboptimal financial management. These issues can hinder the success of credit programs and lead to financial difficulties for both the bank and the borrowers. As a solution, BTN has strengthened its monitoring system to closely track the loan usage and repayment process. Additionally, BTN provides financial education programs to customers to enhance their understanding and improve financial management, aiming to minimize the risk of bad credit and ensure the sustainability of construction projects.